2003
DOI: 10.2113/gscanmin.41.2.293
|View full text |Cite
|
Sign up to set email alerts
|

Major- And Trace-Element Analysis of Sulfide Ores by Laser-Ablation Icp Ms, Solution Icp Ms, and Xrf: New Data on International Reference Materials

Abstract: International reference materials representing a diverse suite of sulfide ores and related lithologies have been analyzed for major and trace element concentrations by XRF, solution ICP-MS, and laser-ablation ICP-MS (LA-ICP-MS) after fusion of the sample to a lithium borate glass. Reference materials analyzed for this study include a wide variety of bulk compositions, including ores of Pb-Zn sulfides, Fe sulfides, Cu-Mo sulfides, and silicate matrices. Concentrations of 33 elements were determined, including l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 17 publications
0
31
0
1
Order By: Relevance
“…Use of appropriate matrix-matched reference standards is critical to enable correction for laser-induced fractionation during ablation, and thus reliable and reproducible quantitative outcomes (e.g., [25][26][27][28][29][30][31][32]). Table 1 lists reference materials commonly employed for LA-ICP-MS trace element analysis, matrices for which they have been applied, and key references regarding their suitability.…”
Section: Reference Materials and Matrix Effectsmentioning
confidence: 99%
“…Use of appropriate matrix-matched reference standards is critical to enable correction for laser-induced fractionation during ablation, and thus reliable and reproducible quantitative outcomes (e.g., [25][26][27][28][29][30][31][32]). Table 1 lists reference materials commonly employed for LA-ICP-MS trace element analysis, matrices for which they have been applied, and key references regarding their suitability.…”
Section: Reference Materials and Matrix Effectsmentioning
confidence: 99%
“…With the exception of the noble metal elements, the trace elements in sulfides could be calibrated against pressedpowder pellets of sulfide (e.g. MASS-1 or MASS-3) [153], glasses of sulfide fused with a lithium borate flux [68,154,155], silicate reference glasses [156,157] or multi-element standard solutions [158]. Košler et al [111] found that a small amount of oxygen released from the sample during the laser ablation process can also affect the elemental fractionation.…”
Section: Metal Oxides and Metal Sulfidesmentioning
confidence: 99%
“…Instead it has been employed for analyses of sulfur in sulfide minerals, where the S + / O 2 + ratio is very high, and in particular where sulfur was measured only as the internal standard element for ablation-yield corrections (e.g., Ballhaus and Sylvester 2000;Cabri et al 2003;Wohlgemuth-Ueberwasser et al 2007). Norman et al (2003) used this method to measure sulfur concentrations of 1.7 to 37 wt% in sulfide ore reference materials prepared with lithium borate as fused glass discs, applying 57 Fe as the internal standard isotope, on 100-μm diameter ablation spots. They reported detection limits for sulfur of 0.55 wt%, precisions of better than Notes: The isotopic mass data are from Audi et al (2003).…”
Section: Analyses Of the Sulfur Concentration Of Minerals And Glassesmentioning
confidence: 99%